2019
DOI: 10.1177/1040638719877916
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Bcl-2 expression in feline follicular lymphomas

Abstract: Bcl-2, an anti-apoptotic protein, is commonly overexpressed in follicular lymphomas in humans. This is usually the result of a chromosomal translocation that transposes the Bcl-2 gene into the immunoglobulin gene locus. The immunohistochemical assessment of this overexpression can be used as a tool for the differentiation of follicular lymphoma and follicular hyperplasia. In cats, little information about the expression of Bcl-2 in follicular lymphoma exists. We investigated 18 follicular lymphomas histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…The upregulation of this protein in some tumoral cells limits the activation of caspases, prevents cell death, and confers longevity to neoplastic cells [24,28]. This upregulation observed in some human lymphomas has paralleled recent research in veterinary medicine regarding Bcl-2 immunoexpression in feline lymphomas [24][25][26]28]. These studies showed that T-cell lymphomas were more likely to express this Bcl-2 oncoprotein compared with B-cell lymphomas [24][25][26]29,30].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The upregulation of this protein in some tumoral cells limits the activation of caspases, prevents cell death, and confers longevity to neoplastic cells [24,28]. This upregulation observed in some human lymphomas has paralleled recent research in veterinary medicine regarding Bcl-2 immunoexpression in feline lymphomas [24][25][26]28]. These studies showed that T-cell lymphomas were more likely to express this Bcl-2 oncoprotein compared with B-cell lymphomas [24][25][26]29,30].…”
Section: Introductionmentioning
confidence: 90%
“…The B-cell lymphoma gene-2 (bcl-2) encodes the Bcl-2 protein-an anti-apoptotic factor that preserves the survival in non-proliferating cells, promoting DNA reparation [24][25][26][27]. The upregulation of this protein in some tumoral cells limits the activation of caspases, prevents cell death, and confers longevity to neoplastic cells [24,28].…”
Section: Introductionmentioning
confidence: 99%
“…BCL-2 was found in one study to be expressed in 11 of 21 feline lymphoma tumors (as opposed to no BCL-2 expression in SCC tumors), and expression of the gene was higher in T-cells than B-cells [44]. However, another study showed lack of BCL-2 expression in follicular lymphomas [45]. Because the BCL-2 family of genes regulates apoptosis, with BCL-2 (along with BCL-XL and BCL-W) acting as an apoptosis inhibitor through inhibition of cytochrome C and AIF release, which would then activate caspases leading to apoptosis [46], dysregulated BCL-2 may lead to extended cell survival and resistance to lymphoma therapies seeking to initiate apoptosis [44].…”
Section: Lymphomamentioning
confidence: 97%
“…Once the balance breaks, it may lead to various neurodegenerative diseases with a fundamental pathological feature of cell death, such as strokes with a high number of neurons dying by necrosis (Tian et al, 2019;Zhou et al, 2020). Some researchers have Karamitopoulou et al, 2007;Farnebo et al, 2011;Omori et al, 2011;Sen et al, 2015;Heng et al, 2016;Bani-Ahmad et al, 2018;Chen et al, 2019;Henrich et al, 2019;Moledina et al, 2019;Schiffmann et al, 2019 Prognostic Bcl-2, Bax, p53, Fas, FasL, caspase-2, caspase-3, caspase-7, caspase-8, caspase-9, TNF-α, DNA fragmentation, Bak, Bok, Bim, PUMA, PMAIP1, MCL1, BCL2L10, TRAIL, TRAIL-R1/2/3, c-FLIP, IAPs Feng et al, 2018;Huang K.H. et al, 2018 Necroptosis Diagnostic NLRP3, AUNIP, RIPK1/3 He et al, 2016;Lee et al, 2016;Yang Z. et al, 2019 Prognostic NLRP3, MLKL, RIPK1/3, TLR3/TICAM1, AURKA Yuan et al, 2015;Yao et al, 2017;Conev et al, 2019;Soleymani Fard et al, 2019;Sun et al, 2019;Malhotra et al, 2020 Autophagy Diagnostic LC3, Na+/K+-ATPase, mTOR Mijatovic et al, 2012;Mete et al, 2018;Sui et al, 2018 Prognostic LC3, ATG, BECN1, Na + /K + -ATPase, AMPK, mTOR Cao et al, 2016;Cheng et al, 2016;Schläfli et al, 2016;Gajate et al, 2018;Guo et al, 2019 Ferroptosis Diagnostic GPX4, ALOX15, SLC7A11, BAP1, HSP90, HSPB1, FANCD2, TP53 Kamal et al, 2004;Guerriero et al, 2015;Saif et al, 2016;Hui et al, 2017;…”
Section: Rcds Detection In Clinic Usagementioning
confidence: 99%